Practical deployment of Cisco Identity Services Engine (ISE) : real-world examples of AAA deployments - Richter, Andy; Wood, Jeremy (Syngress, 2016)
Sharing their expertise from dozens of real-world implementations of ISE and the methods they have used for optimizing ISE in a wide range of environments, the authors of this book shows you how to deploy ISE with the necessary integration across multiple different technologies required to make ISE work like a system. --